Law Enforcement Against Criminal Acts Of Car Sale And Purchase Fraud (Court Case Study Cibinong) - Nasution, Iyus Midar; Hartini, Sri; Ferrary, Ande Aditya Iman (Universitas Ibn Khaldun Bogor, 2025)
Indonesia is a country based on law. Therefore, every act that is contrary to Pancasila and the 1945 Constitution (UUD) is considered the most fundamental legal basis, along with various other legal products. The law must always be enforced to achieve the ideals and objectives of the Indonesian State, as stated in the preamble to the fourth paragraph of the 1945 Constitution which outlines the formation of a government aimed at protecting the entire Indonesian Nation and all Indonesian bloodshed, as well as to advance general welfare, increase the nation's intelligence, and participate in maintaining world order based on the principles of independence, eternal peace and social justice. The type of research used is normative juridical as the main approach. This means that a legal approach is taken by examining theories, concepts, as well as reviewing statutory regulations that are relevant to this research. Normative juridical research places law as a system of norms, which includes principles, norms, rules from statutory regulations, agreements, and doctrine (teachings). This normative research focuses on legal systematics with the main aim of identifying understandings or basics in the law. Judges have an obligation to investigate, uphold and understand the legal ideals that develop in society in their role as law enforcers and dispensers of justice. Judges must actively participate in society in order to understand, feel and appreciate the sense of justice and the laws that apply therein. In this way, the judge can make decisions that are in accordance with the law and do not take sides with anyone. The judge's considerations in sentencing the defendant in the Cibinong District Court decision Number 72/Pid.B/2022/PN Cbi, are based on the following matters: stating The Defendant Anugrah Hidayat Bin Aan Sutarna has been legally and convincingly proven guilty of committing the crime of Fraud. of the sentence imposed, Determine the Defendant to remain in detention, Determine the evidence in the form of: 1 (one) Receipt for receipt of Rp. 85,000,000.00 (eighty five million rupiah) dated 12 September 2021, Photocopy of STNK, 1 ( one) Bogor City Police Samsat Counter I Registration Note sheet dated July 8 2021 (STNK in process), Current Account from Bank Syariah Bogor an. Nurul Nuraini Period 1 July 2021 to 31 July 2021, 1 (one) sheet of Minutes of Handover of Toyota Avanza Car No.Pol.: F-1806-DB from 8 BCA Finance, Photocopy of KTP of Mr. Anugrah Hidayat, SE Still attached to the case file, Charges the Defendant to pay court costs of Rp. 5,000.00 (five thousand rupiah).